Disappointment aversion and social comparisons in a real-effort competition - Gaechter, Simon; Huang, Lingbo; Sefton, Martin (Wiley, 2018)
We present an experiment to investigate the source of disappointment aversion in a sequential real-effort competition. Specifically, we study the contribution of social comparison effects to the disappointment aversion previously identified in a two-person real-effort competition (Gill, D., and V. Prowse. “A Structural Analysis of Disappointment Aversion in a Real Effort Competition.” American Economic Review, 102, 2012, 469–503). To do this we compare “social” and “asocial” versions of the Gill and Prowse experiment, where the latter treatment removes the scope for social comparisons. If disappointment aversion simply reflects an asymmetric evaluation of losses and gains we would expect it to survive in our asocial treatment. Alternatively, if losing to or winning against another person affects the evaluation of losses/gains, as we show would be theoretically the case under asymmetric inequality aversion, we would expect treatment differences. We find behavior in social and asocial treatments to be similar, suggesting that social comparisons have little impact in this setting. Unlike in Gill and Prowse we do not find evidence of disappointment aversion. (JEL C91, D12, D81, D84)